Late onset autosomal dominant cerebellar ataxia a family description and linkage analysis with the hla system - Walter O. Arruda; M. Luiza Petzl-Erler; Moema A. Cardoso; Thomas Lehner; Jurg Ott (Arquivos de Neuro-Psiquiatria)
A family suffering an autosomal dominant form of late onset hereditary cerebellar ataxia is described. Eight affected family members were personally studied, and data from another four were obtained through anamnesis. The mean age of onset was 37.1±5.4 years (27-47 years). The clinical picture consisted basically of a pure ataxic cerebellar syndrome. CT-scan disclosed diffuse cerebellar atrophy with relative sparing of the brainstem (and no involvement of supratentorial structures. Neurophysiological studies (nerve conduction, VEP and BAEP) were normal. Twenty-six individuals were typed for HLA histocompatibility antigens. Lod scores were calculated with the computer program LINKMAP. Close linkage of the ataxia gene with the HLA system in this family could be excluded - 0==0,02, z=(-2,17) - and the overall analysis of the lod scores suggest another chromossomal location than chromosome 6.